Er:YAG laser suppresses pro-inflammatory cytokines expression and inflammasome in human periodontal ligament fibroblasts with Porphyromonas gingivalis-lipopolysaccharide stimulation - Min Yee Ng; Taichen Lin; Szu-Han Chen; Yi-Wen Liao; Chia-Ming Liu; Cheng-Chia Yu (Elsevier, 2024)
Background/purpose: Periodontitis is an inflammatory condition of the tooth-supporting structures triggered by the host's immune response towards the bacterial deposits around the teeth. It is well acknowledged that pro-inflammatory interleukin (IL)-6, IL-8, MCP-1 as well as the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome, are the key modulators in the activation of this response. Erbium-doped yttrium-aluminium-garnet (Er:YAG) laser, a solid-state crystal laser have been commonly used in the treatment of periodontal diseases. However, little is understood about the molecular mechanism of the Er:YAG laser, especially in targeting the host immune response brought on by periodontal pathogens. Hence, the current study focused on the protective effects of Er:YAG laser on periodontitis in-vitro in terms of pro-inflammatory cytokines, chemokines and NLRP3 inflammasome expressions. Materials and methods: Human periodontal ligament fibroblast (PDLFs) were first stimulated with lipopolysaccharides (LPS) from P. gingivalis (Pg-LPS) to simulate periodontitis. Cells were then irradiated with Er:YAG laser of ascending energy densities (3.6-6.3 J/cm2), followed by cell proliferation and wound healing assay. Next, the effects of Er:YAG laser on the expressions of IL-6, IL-8, MCP-1, NLRP3, and cleaved GSDMD were examined. Results: Pg-LPS was found to reduce cell's proliferation rate and wound healing ability in PDLFs and these were rescued by Er:YAG laser irradiation. In addition, LPS stimuli resulted in a marked upregulation in the secretion of IL-6, IL-8 and MCP-1 as well as the mRNA and protein expression of NLRP3 and cleaved-GSDMD protein whereas Er:YAG laser suppressed the elicited phenomena. Conclusion: To our knowledge, this is the first study to look into the laser's implication on the NLRP3 inflammasome in periodontitis models. Our study reveals a crucial role of Er:YAG laser in ameliorating periodontitis in-vitro through the modulation of IL-6, IL-8, MCP-1 and the NLRP3 inflammasome and highlights that the control of the NLRP3 inflammasome may become a potential approach for periodontitis.